KEBIJAKAN POLITIK PENGENDALIAN DAN PENGAWASAN MINUMAN BERALKOHOL DI JAKARTA BERDASARKAN PERATURAN PRESIDEN NO. 74 TAHUN 2013 - Lusi Andriyani (SWATANTRA, 2017)
The formulation of the policies used community still has not put the development instrument oriented to the needs of the community. One of them is the enactment of Presidential Decree no. 3 of 1997 which only regulate limitation of liquor. These conditions encourage community organizations such as FPI who concentrate on the disobedience to file a retest of the material against.  Presidential Regulation no. 74 of 2013 on the Control and Supervision of Alcoholic Beverages to the Supreme Court. The emergence of Presidential Regulation no. 74 of 2013 has not been able to minimize the circulation of alcohol in the community, it is increasingly alarming. Such conditions encourage government efforts to relax the Perpres. The realization of the policy of relaxing the old rules is to authorize to determine which areas can sell  liquor.  With  the  relaxation  of  these  rules  the local government will have the authority to deter- mine which areas can sell it. This policy is done because the Local Government is considered the most knowledgeable about which locations require the permission to sell liquor. By relaxing the rules, it does not mean that li- quor class A can be resold in mini market, becau- se the prohibition of beer sales is still regulated in the Minister of Trade Regulation no. 6/2015 on the second amendment toMinister of Trade no. 20 /M-DAG/4/2014 concerning Control and Supervi- sion distribution and sale liquor.Keywords: Miras, FPI, Policy.